Perbincangan Fans Mengenai Performa Klub Sepakbola Arsenal (Studi Netnografi Highlights Pertandingan Arsenal di YouTube) - Adhitya, Nandi (Dinasti Research, 2024)
The aim of this research is to find out and analyze whether the reaction to discussion of Arsenal's performance consistently follows Arsenal's performance in the match or is the opposite of Arsenal's performance, and also to analyze how the discussion is on the big accounts of Arsenal fans and the trend of words used in performance discussions. Arsenal and also a look at the culture of football conversation on YouTube as a whole. The method used in this research is netnography. This research was carried out by observing conversations between Arsenal fans on Arsenal's official account on the YouTube social media platform. The object of this research is 3 video highlights of Arsenal matches with different scores. The results of the research show that of all the comment columns that have been studied, the discussion pattern or trend of discussion about Arsenal in the match highlight comment column on YouTube is a pattern that tends to be positive, where any moment or incident in the match is faced and responded to with a positive outlook.